Highly efficient and selective conversion of guaiacol to cyclohexanol over Ni-Fe/MgAlOx: Understanding the synergistic effect between Ni-Fe alloy and basic sites. (1st November 2022) - Huang, Lei; Tang, Feiying; Liu, Pingle; Xiong, Wei; Jia, Shangkun; Hao, Fang; Lv, Yang; Luo, Hean
Graphical abstract: Highlights: Ni-Fe alloy supported catalysts were prepared from layered double hydroxide precursor. Ni-Fe alloy sites facilitate the aromatic ring hydrogenation. Alkaline MgAlOx support promotes the demethoxylation and suppresses the dehydroxylation. Synergistic effect between Ni-Fe alloy and basic sites improves cyclohexanol selectivity. Abstract: The production of cyclohexanol from non-fossil biomass is green and sustainable. Here, a series of highly dispersed Ni-Fe alloy nanocatalysts (Ni-Fe/MgAlOx ) were prepared for guaiacol hydrodeoxygenation to cyclohexanol. The results show that the doped Fe led to electron-rich Ni and the introduced Mg species of the support increased the basic sites. The kinetic studies indicate that guaiacol conversion to cyclohexanol included the aromatic ring hydrogenation and the demethoxylation steps. And the Ni-Fe/MgAlOx-1 with the sites of Ni-Fe alloy could significantly reduce the Ea of aromatic ring hydrogenation. Meanwhile, the Ni-Fe/MgAlOx-1 with Mg-doped support exhibited much lower Ea of demethoxylation. Thus, the synergistic effects between Ni-Fe alloy and basic sites brought about high performance to cyclohexanol. Hence the Ni-Fe/MgAlOx-1 gave the highest cyclohexanol yield of 92.1%. The strategy of optimization different catalytic sites for the corresponding reaction step can provide a particular view for designing efficient catalysts in multiple-step hydrogenation/hydrodeoxygenation reactions.